PEMBENTUKAN KARAKTER ANAK USIA DINI MELALUI PEMBIASAAN SHOLAT DHUHA TERHADAP MORAL DAN AGAMA DI PAUD - Husnul Hotimah; Dinar Azzahra; Fadhilah Azzahra; Andri Hardiyana (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
Formation of Early Childhood Character through the Practice of Dhuha Prayer on Morals and Religion in PAUD. This research aims to analyze the impact of the habit of Dhuha prayers on the development of religious character in early childhood. The research method used was descriptive qualitative, with observation, interview and documentation techniques in one PAUD in the 5-6 year age group. The practice of Dhuha prayers is carried out regularly using a hands-on practical approach, including teaching the procedures for worship, reading prayers and memorizing short letters. The research results show that the habit of Dhuha prayers has a significant impact on children's character development, especially in the aspects of discipline, responsibility and religiosity. Children become more organized in managing time, understand religious obligations, and internalize religious values in everyday life. Despite facing challenges such as children's low concentration, support from teachers and parents succeeded in creating a conducive environment. This research concludes that the habit of Dhuha prayers in PAUD is an effective strategy in forming children's religious character from an early age, which functions as a strong moral foundation for their future lives. keywords: early childhood, Dhuha prayer, habituation, moral, religion